IMPLEMENTATION OF DECISION SUPPORT SYSTEMS TO DETERMINE THE CANDIDATE OF JAKARTA PINTAR CARD RECIPIENT WITH PROMETHEE METHOD - Fikki Muhamad (LPPM, 2019)
ABSTRACTJakarta Smart Card (KJP) is a strategic program to provide access for DKI Jakarta residents from disadvantaged communities to get a minimum education up to graduating from high school / vocational school with full funding from the DKI Jakarta Provincial Budget. In determining KJP recipients, the SMK WISATA INDONESIA feels the need to create a mentoring program to select prospective KJP recipient students with criteria set by the school. There fore a suitable method is needed to solve the problem, one of the right methods is the Preference Ranking of the Organization Method for Enrichment Evaluation (PROMETHEE). This method was chosen because Promethee is a method of determining sequence (priority) in multi criteria analysis. The main problem is simplicity, clarity, and stability. The presumption of the dominance of the criteria used in promethee is the use of values in outranking relationships. The application of this method resulted in the selection of prospective KJP recipients based on certain criteria (multi criteria) so that the determination of KJP candidate recipient students was more on target, from the results of the study obtained the ranking composition or rank of prospective KJP recipients who have the highest to lowest eligibility Based on the value obtained from the calculation of Net Flow from each alternative / prospective KJP recipient student, the highest Net Flow means that it is recommended to receive KJP, because it is estimated that the most suitable as KJP recipient